PENINGKATAN PRODUKTIVITAS LAHAN PODZOLIK MERAH KUNING MELALUI PEMUPUKAN PUPUK HIJAU FLEMENGIA CONGESTA DAN KAPUR DOLOMIT - Djamhari, Sudaryanto (BPPT)
The obyektive of the researcah is to know the effect of to the land fertility, regarded to soybeen production. The reserch use Complete Randemize Disign With One Way Analysis of Variance, Regression, and Correlation in order to know the effect of treatment to the land fertility. The research was carried out in Wonoharjo Village, Unit VIII Kuro Tidur Transmigration area, Bengkulu, during three planting season from 1999 to 2000. The result of the research showed that Flemengia congesta as a fence crop or hedgerows was segnifi cant to land fertility through improvement of nutriens availability, increasing pH, decreasing availability of aluminium (Al). The effect of organic matter from prunning ofthe hedgerows into the soil a high of 5,0 ton/ha will increase average soybenn production from 13,974 kw (dry grain) to 18,176 kw/ha or increase 30,07 %, whereas the effect of organic matter 5,0 ton/ha combained with dolomit 2,5 ton/ha will increase 43,00 %. The effect of organic matter 10,0 ton/ha combined with dolomit 2,5 ton/ha will increase average soybeen production from 13,974 kw/ha or increase 57,19%.Keywords: red yellow podzolic land, organic matter, dolomit, land produktivitas